ECONOMIC, POLITICAL AND INSTITUTIONAL DETERMINANTS OF FISCAL DEFICIT - Vukovic, Marija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
This paper seeks basic economic and political causes of instability and rising fiscal deficit. Economic factors that may cause the appearance and increase in the fiscal deficit are: growth of current public spending, launching public investments, tax cuts and weakening financial discipline. The government's policies are a result of its coalition agreement, everywhere in the world, is the primary factor that causes the formation and growth of the fiscal deficit. The aim is to show that the politically unstable countries with weak institutions, often vulnerable to fiscal shocks, which, in turn, lead to greater instability in the fiscal deficit.